An Internet of Things (IoT) Based Block Chain Technology to Enhance the Quality of Supply Chain Management (SCM) - Rizwan, A. (2022)
Recent technological developments indicate possible advancements in supply chain management (SCM). ese innovations have attracted a lot of interest from industries including logistics, manufacturing, packaging, and transportation. e conventional systems, however, use centralised servers to control all operations, including the exchange of raw materials, making orders, dealing with buyers and sellers, and updating orders. e network’s supply chain may thus be insecure as a result of every activity being routed via centralised servers. e danger is additionally increased by a number of di culties, including scalability, data integrity, security, and availability. Block chain technology may be used in these circumstances to decentralise transaction processing and eliminate the need for a centralised controller. In this approach, the performance of the resource-constrained supply chain network is improved by the e ective use of edge computing and priority data access. e Intelligent K-Means (IKM) clustering algorithm is suggested across the edge nodes in the current research to categorise the priority level of each piece of data. is classi er determines if the edge node has received data that is high priority or low priority. Low priority data is recorded in the log les for future data analysis. en, to allow safe data ow in the open block chain while excluding outside parties, the High Priority Access based Smart Contract (HPASC) technique is deployed. e whole experiment was conducted in a Python environment, and variables including scalability, reaction time, throughput, and accuracy were studied. Current systems’ constrained block sizes and fork creation lengthen the time transactions must wait before being processed. e suggested methodology is quicker and uses less storage space than current block chain systems. e results show that the suggested approach works better than current blockchain technology to raise the standard of supply chain management.